Does Social Policy Matter? Poverty Cycles in OECD Countries - Olli Kangas; Joakim Palme (Luxembourg Income Study (LIS), 1998)
The purpose of this paper is twofold, partly exploratory; to determine the degree to which Rowntree's poverty cycles are still apparent among the most advanced industrial nations, and partly analytical; to examine how successful different sociopolitical strategies have been in eliminating poverty over the life-cycle. The paper seeks to make a contribution in relation to earlier studies by both examining changes within singular countries and by comparing trends cross-nationally provisions.
Keywords: 330; Armut; Lebenszyklus; Sozialpolitik; OECD-Staaten